The role of helminths and their antigens in cancer therapy: insights from cell line models - Gita Alizadeh; Ali Kheirandish; Maryam Alipour; Mahnaz Jafari; Mahdis Radfar; Tina Bybordi; Raheleh Rafiei-Sefiddashti (Infectious Agents and Cancer, 2024)
Abstract Background Recent articles have explored the effect of worms on cancer cells. This review focused on various cell cultures employed to understand which cells are more commonly and less utilized. Methods The present review analyzed studies published between 2013 and 2023 to obtain information about different cell cultures used in cancer studies involving helminths. Databases such as PubMed, Google Scholar, HINARI, and the Cochrane Library were searched. Results This search yielded 130 records, but 97 papers were excluded because they were either irrelevant to the research topic (n = 72) or contradicted the research idea (n = 25).The remaining twenty-one articles focused on different types of worms, such as Echinococcus granulosus, Clonorchis sinensis, Opisthorchis felineus, Opisthorchis viverrini, Trichinella spiralis, Toxocara canis, and Heligmosomoides polygyrus. Conclusion Due to the presence of numerous antigens, parasites at different growth stages can impact various cells through unknown mechanisms. Given the high diversity of antigens and their effects, artificial intelligence can assist in predicting initial outcomes for future studies.